Unsheltered - Kingsolver, Barbara (New York : HarperCollins, 2018)
Willa Knox has always prided herself on being the embodiment of responsibility for her family. Which is why it's so unnerving that she's arrived at middle age with nothing to show for her hard work and dedication but a stack of unpaid bills and an inherited brick home in Vineland, New Jersey, that is literally falling apart. The magazine where she worked has folded, and the college where her husband had tenure has closed. The dilapidated house is also home to her ailing and cantankerous Greek father-in-law and her two grown children: her stubborn, free-spirited daughter, Tig, and her dutiful debt-ridden, ivy educated son, Zeke, who has arrived with his unplanned baby in the wake of a life-shattering development. In an act of desperation, Willa begins to investigate the history of her home, hoping that the local historical preservation society might take an interest and provide funding for its direly needed repairs. Through her research into Vineland's past and its creation as a Utopian community, she discovers a kindred spirit from the 1880s, Thatcher Greenwood.
Keywords: Vineland (N.J.) -- Fiction; Domestic fiction; Historical fiction